Using professional certification criteria to assess occupational safety curricula in degree programs investigating accreditation - Todd William Loushine; Robert G. Feyen (Laureate Education Inc, 2013)
The aim of this paper is to demonstrate a novel assessment method developed to determine if the curriculum from two separate safety degree programs provided sufficient opportunity for students to obtain the knowledge required for professional practice in occupational safety. The method relies on the Board of Certified Safety Professionals (BCSP) examination blueprints. In the graduate program case study, over 88% of the BCSP criteria were met through an explicit means and up to 64% through assignments or better. Aggregating criteria into respective subject areas showed that the curriculum covered anywhere from 58% to 100% of the items within each BCSP topic. In the undergraduate case study, over 96% of the BCSP criteria through an explicit means, and 82.8% of knowledge items were assessed in assignments, exams or better. Aggregating criteria into respective subject areas showed that the curriculum covered anywhere from 75% to 100% of the items within each BCSP topic. Once briefed on the results, all faculty/instructors agreed that the approach helped identify strengths and weaknesses in their current curriculum. Most importantly, presentation of results acted as a catalyst for curricular discussions amongst the faculty that resulted in improvement priorities and a better understanding of student learning potential in course assignments. DOI: 10.18870/hlrc.v3i2.113